2023
DOI: 10.1073/pnas.2301360120
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the liver’s neuroprotective role ameliorates traumatic brain injury pathology

Abstract: Traumatic brain injury (TBI) is a pervasive problem worldwide for which no effective treatment is currently available. Although most studies have focused on the pathology of the injured brain, we have noted that the liver plays an important role in TBI. Using two mouse models of TBI, we found that the enzymatic activity of hepatic soluble epoxide hydrolase (sEH) was rapidly decreased and then returned to normal levels following TBI, whereas such changes were not observed in the kidney, heart, spleen, or lung. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…However, based on similar changes not only in D-to-E ratios but also in EpFA and diol levels between plasma and the liver (Figure 2), together with the hepatic capacities to generate EpFAs and diols and exchange metabolites with plasma, as discussed above, we believe the liver may be the tissue driving all these changes. Similar conclusions were recently drawn based on studies with hepatocyte selective sEH knockouts or sEH reduction associated with brain injuries [25,26].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, based on similar changes not only in D-to-E ratios but also in EpFA and diol levels between plasma and the liver (Figure 2), together with the hepatic capacities to generate EpFAs and diols and exchange metabolites with plasma, as discussed above, we believe the liver may be the tissue driving all these changes. Similar conclusions were recently drawn based on studies with hepatocyte selective sEH knockouts or sEH reduction associated with brain injuries [25,26].…”
Section: Discussionsupporting
confidence: 80%
“…This intriguing possibility needs to be directly tested in future studies. Hepatic-sEH activity was decreased without changes in sEH proteins during brain injuries [26].…”
Section: Discussionmentioning
confidence: 94%
“…Mechanically damaged neurons in TBI patients often experience a loss of biological function, leading to cognitive impairment. It is crucial to identify a medication that can prevent the death of damaged neurons while preserving their normal activity ( Dai et al, 2023 ; Yang et al, 2024 ). TGF-β1, a cytokine involved in regulating various cellular pathways, has shown multiple benefits in TBI treatment by contributing to immune regulation in traumatic brain injuries.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a possible mechanism through which the liver’s metabolic regulatory functions could contribute to the overall protection of the brain during ischemic insults. Previous studies have demonstrated that hepatic soluble epoxide hydrolase (sEH) activity was specifically altered following traumatic brain injury (TBI) and negatively correlated with the plasma levels of 14,15,-epoxyeicosatrienoic acid, which shows neuroprotective effects in the controlled cortical injury mouse model 30 . Hepatic sEH activity also plays roles in regulating cerebral Aβ metabolism and the pathogenesis of Alzheimer’s disease in mice 31 .…”
Section: Discussionmentioning
confidence: 99%